2023
DOI: 10.3390/jcm12051855
|View full text |Cite
|
Sign up to set email alerts
|

Giant Juvenile Fibroadenoma: Case Report and Review of the Literature

Abstract: Fibroadenomas are common benign breast tumors. Fibroadenomas that exceed 5 cm in diameter, weigh more than 500 g, or replace more than four-fifths of the breast are characterized as giant. A fibroadenoma diagnosed in patients during childhood or adolescence is characterized as juvenile. An extensive PubMed search of the literature in English up until August 2022 was performed. In addition, a rare case of a gigantic fibroadenoma in an 11-year-old premenarchal girl who was referred to our adolescent gynecology c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…It is evidenced by the histological structure of FAM, similar to hyperplastic breast lobules, where the FAM responds to a hormonal stimulus [24]. This opinion is in line with the study of Matz et al, which suggested that women at the age of 15-25 years, or what is known as menarche, can have FAM lumps in their breasts due to the link between lobule sensitivity and reproductive hormones which are risk factors for FAM [39].…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…It is evidenced by the histological structure of FAM, similar to hyperplastic breast lobules, where the FAM responds to a hormonal stimulus [24]. This opinion is in line with the study of Matz et al, which suggested that women at the age of 15-25 years, or what is known as menarche, can have FAM lumps in their breasts due to the link between lobule sensitivity and reproductive hormones which are risk factors for FAM [39].…”
Section: Resultssupporting
confidence: 69%
“…When women age, the FAM lump will shrink and even disappear. A decrease in the response of reproductive hormones causes it [20,2,39]. Therefore, women who suffer from FAM and are approaching menopause must be given as clear information as possible about the link between FAM and menopause so that they can review the management that will be carried out [17].…”
Section: Resultsmentioning
confidence: 99%
“…It constitutes 30 to 50 % of breast masses. When it exceeds 5 cm, weighs more than 500 g, or occupies more than 4/5 of the breast, it is considered as giant [ 3 ]. This form is rare and constitute 0.5 % - 4 % of all fibroadenomas cases.…”
Section: Discussionmentioning
confidence: 99%
“…In its giant form, this mass tends to deform the breast, causing aesthetic discomfort [ 1 , 4 ]. Despite the rapid evolution of the mass, the general condition is preserved, and general symptoms are absent [ 3 ]. In our case, the mass had rapidly increased in size within two months, causing significant discomfort and fear for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining breast tissue gradually fills the empty space after tumor excision, eliminating the need for further reconstructive procedures. However, large juvenile fibroadenoma lesions can compress the surrounding healthy breast tissue, complicating accurate assessment of the unaffected parenchyma [12,13].…”
mentioning
confidence: 99%